Native American Landscapes : An Engendered Perspective - Claassen, Cheryl, 1953- (Book collections on Project MUSE., 2016)
"This manuscript is an edited collection of essays focusing on archaic and prehistoric North America. Cheryl Claassen argues that specifically focusing on an engendered landscape study allows the contributors to raise issues of women's mobility, fertility, retreat locations, pilgrimages, and an overall exploration of the customarily different tasks undertaken by native men and women. The collection explores a range of sites throughout North America, including locations such as the Mojave Desert, the Mississippi River Valley, the Cumberland Plateau, and the Northwest coast, among others."--Provided by publisher.